Impact of a Nursing Intervention Bundle of Care on Nasal-CPAP-Related Nasal Injuries in Preterm Infants: A Quality Improvement Initiative - Mohamed, Mohab; Noaman , Ahmed; Nour, Islam; Abdel-Hady, Hesham (Open Access Macedonian Journal of Medical Sciences, 2023)
AIM: The objective is to assess the effect of the application of a nasal injury prevention bundle on the incidence and severity of nasal-continuous positive airway pressure (nCPAP)-related nasal injuries in preterm infants. METHODS: We conducted a prospective controlled before-after study in a preterm neonate, <37 weeks gestation, who required nCPAP in the neonatal intensive care unit, at Mansoura University Children’s Hospital, between September 2018 through October 2019. After 2 months of nursing staff training, a nasal trauma prevention bundle was implemented. The nursing intervention bundle comprised nasal barrier dressing, regular focused checking for evolving nasal skin injury, and proper application of the CPAP device. nCPAP-related nasal injuries per 1000 days and grading of nasal injury severity were the primary outcomes. Time to onset of nasal injury after initiation of CPAP; duration of nCPAP use, duration of oxygen dependency; incidence of pneumothorax, broncho-pulmonary dysplasia; intraventricular hemorrhage; periventricular leukomalacia; late-onset sepsis; length of hospital stay; and in-hospital mortality were the secondary outcomes. RESULTS: Data from 62 preterm neonates were analyzed (31 in each group). The nasal trauma prevention bundle of care was associated with reduced nasal injury incidence per 1000 nCPAP-days (140 vs. 148.94, p = 0.03) with improved nasal injury severity staging (p = 0.003) compared to the pre-bundle era. Nasal injury developed earlier in the control group (1 [1–1] vs. 2 [1–3] days, p = 0.002) compared to the intervention group. No statistically significant differences were reported between groups regarding any of the other secondary outcomes. Longer duration of CPAP use (p = 0.009) and lack of bundle application (0.03) were the independent risk factors associated with nCPAP-related nasal injuries in preterm neonates. CONCLUSION: The implementation of a bundle of nursing interventions is associated with a substantially improved incidence and severity of nasal injuries in preterm infants receiving nCPAP.